Fundamentals and Understanding of the Democratic System in Thailand - Shatnataphat, Chattawat (Kalágatos, 2025)
This research aims to: 1) understand democracy's fundamentals in Thailand; 2) identify sources of democratic understanding and interpretation; 3) study the essentials for establishing a stable democratic system. A mixed-method approach was used, combining qualitative and quantitative methods. In-depth interviews and document analysis were conducted, alongside a survey of 1,165 Bangkok citizens. The study found that the general population has a basic understanding of democracy, emphasizing regular elections as a key component. Income significantly affects understanding, while factors like sex, age, education, and marital status do not. The foundations of democracy, particularly freedom and participation, are well comprehended. However, not all elements are equally understood. A sustainable democratic system prioritizes just governance. These findings are crucial for developing policies and strategies to enhance democratic understanding and support in Thailand.